Stagnation of the Pensilungpa glacier, western Himalaya, India: causes and implications. Issue 268 (13th April 2022) - Garg, Purushottam Kumar; Garg, Siddhi; Yousuf, Bisma; Shukla, Aparna; Kumar, Vinit; Mehta, Manish
Abstract: This study investigates stagnation conditions of the Pensilungpa glacier, western Himalaya. Multiple glacier parameters (length, area, debris extent and thickness, snowline altitude (SLA), velocity, downwasting and ice cliffs) were studied using field measurements (2016–18), high-resolution imagery from GoogleEarth (2013–17) and spaceborne Landsat, ASTER and SRTM data (1993–2017) to comprehend the glacier's current state. Results show a moderate decrease in length (6.62 ± 2.11 m a −1 ) and area (0.11 ± 0.03% a −1 ), a marked increase in SLA (~6 m a −1 ) and debris cover (2.86 ± 0.29% a −1 ) and a slowdown of ~50% during 1993–2016. Notable thinning of −0.88 ± 0.04 m a −1 was observed between 2000 and 2017 showing a similar trend as field measurements during 2016–17 (−0.88 m) and 2017–18 (−1.54 m). Further, results reveal a stagnation of the lower ablation zone (LAZ). Less mass supply and heterogeneous debris growth (6.67 ± 0.41% a −1 ) over the previous decade resulted in slowdown, margin insulation and slope-inversion, leading to stagnation. Stagnation of LAZ caused bulging in the dynamic upper ablation zone and favored the development of supraglacial ponds and ice cliffs. Ice cliffs have grown significantly (48% in number; 41% in area during 2013–17) and their back-wasting now dominates the ablation process.